Monitoring Orang Tua Terhadap Pembayaran Uang Kuliah Dan Absensi Mahasiswa Berbasis SMS Gateway - Rizaldi Rizaldi; Arridha Zikra Syah (JURIKOM (Jurnal Riset Komputer), 2019)
The problem that always occurs in STMIK Royal in each semester is first, the delay in students preparing the Study Plan Card (SPC) due to the late students themselves paying tuition so that the difficulties for study programs in recording student activity data, then harming the students themselves because they are considered absent during not enrolled in lectures. Second, 90% of the students who get the final grade below are enough due to the lack of lecture meetings from the minimum number of meetings that have been determined by the academic, so students must repeat their studies in the next semester. This situation forces the study program section to be able to condition schedules, classes, and lecturers for students who repeat. For this reason, a monitoring system for tuition payments and student attendance is required based on the SMS Gateway. Through this system, academic parties can disseminate information on tuition payments and student attendance to parents or parents to monitor tuition payments and student attendance through services provided by the system.